"Expanding Ethical Pedagogy in Technical Communication: Learning from Killer Nanobots". Issue 2 (3rd April 2022) - Duncan, Mike
ABSTRACT: Attention to the ethical dimension in technical and professional communication (TPC) is paramount, especially when dealing with new, emerging technologies. Such technologies frequently rest within corporate environments that may resist ethical gatekeeping. I suggest several methods by which TPC instructors can critically question the limits of corporate structure to show students that they have a variety of options for responding to assignments other than those their employers may offer them.